The Positionality and the Promise of Architecture(s) (EAAE Annual Conference Proceedings, 2023)
We are living in an age where the digital avant-garde has been blooming in the practice of architectural discipline. This is an age when the inevitable march of digital technologies, especially the mobilization of artificial intelligence, has increasingly gained momentum. For these reasons, it is even more challenging for architects and researchers to tackle their roles in this tendency.